The impact of Oportunidades on human capital and income distribution: A top-down/bottom-up approach - Debowicz, Darío; Golan, Jennifer (International Food Policy Research Institute, 2013)
In an effort to inform social policy in Mexico, this paper analyzes the effects of a major social program on school attendance and household income distribution, accounting for its partial and general equilibrium effects. Linking a microeconometric simulation model and a general equilibrium model in a bidirectional way, the paper explicitly takes spillover effects of the Oportunidades conditional cash transfer program into account. Our results suggest that partial equilibrium analysis alone may underestimate the distributional effects of the program.